2017
DOI: 10.1111/jocn.13839
|View full text |Cite
|
Sign up to set email alerts
|

Recognising and responding to in‐hospital clinical deterioration: An integrative review of interprofessional practice issues

Abstract: This review presents a unique system-wide approach for exploring how health professionals interprofessionally collaborate in practice to effectively recognise and respond to clinical deterioration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 66 publications
0
24
0
4
Order By: Relevance
“…A further unanticipated and concerning consequence of implementing C4H was the use of the C4H pathway by nurses. Many reports have highlighted that communication problems between health professionals themselves present barriers to effective escalation of care . The described practice by nurses encouraging parents to use C4H to obtain a medical review or even utilizing C4H themselves seems reflective of such interprofessional communication barriers.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A further unanticipated and concerning consequence of implementing C4H was the use of the C4H pathway by nurses. Many reports have highlighted that communication problems between health professionals themselves present barriers to effective escalation of care . The described practice by nurses encouraging parents to use C4H to obtain a medical review or even utilizing C4H themselves seems reflective of such interprofessional communication barriers.…”
Section: Discussionmentioning
confidence: 99%
“…At this point, no specific strategies had been used to address the barrier of overcoming the traditional hospital hierarchy which remains a widely reported issue in escalation of care. [30][31][32][33][34] There were some unexpected findings related to nurse beliefs and behaviours. Despite nurses knowing that there had been only one C4H direct parent MET call since implementation, this concern remained a factor that influenced their decisions to inform parents.…”
Section: Thismentioning
confidence: 99%
See 1 more Smart Citation
“…This was particularly visible in situations when the score was low, but the nurses decided to call based on concerns that something was wrong. In a recent review (Allen, Elliott, & Jackson, ), researchers found that using the RRS led to professional reporting hierarchies and could inhibit the effective recognition of and response to clinical deterioration. This is in line with the finding from our review, indicating that the hierarchical hospital culture may influence nurses’ ability to assess and manage patients in crisis.…”
Section: Discussionmentioning
confidence: 99%
“…This resulted in C4H information not being prioritized when nurses provided information to parents. Difficulties in attempts to bypass the hierarchy and traditional culture in the hospital system are already well‐recognized barriers to health professionals especially nurses effectively utilizing RRS, but had not been previously reported in the context of parent involvement. This is an ironic finding given that the basis and impetus for implementing a process for parent escalation of care is to reduce the delays related to organizational hierarchical behaviours and poor health professional communication …”
Section: Discussionmentioning
confidence: 99%